Exploring the ‘Third Coast’ and ‘Second City’: Background and research on African migration in the Midwestern U.S. and Greater Chicago Metropolitan Area - Taber, C. Kevin (Migration Letters, 2018)
Sub-Saharan African migration to the U.S. is rapidly yet quietly growing, and the Midwestern/Great Lakes region of the country (its “Third Coast”) is becoming an increasingly important destination. In particular, the so-called “Second City” of Chicago – the regional epicenter and third largest U.S. city – is in need of social scientific research addressing the unique trajectories and experiences of its expanding African populations. This paper provides a background for these dynamics by drawing from primary and secondary data on Midwestern African migrant communities’ organizing and activities as observed through interviews and fieldwork among more than fifty African migrant organizations in the Midwestern U.S. and Greater Chicago Metropolitan Area. It will outline the evolution and distribution of African migration in the Chicago area and provide a brief overview of African resources, organizations, and other institutions and establishments as they seek to bring together and represent the burgeoning African community within and beyond the city.